2006
DOI: 10.1093/bja/ael065
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cardiac arrest: a study of 53 718 anaesthetics over 9 yr from a Brazilian teaching hospital

Abstract: Perioperative cardiac arrests were relatively higher in neonates, infants, the elderly and in males with severe underlying disease and under emergency surgery. All anaesthesia-related cardiac arrests were related to airway management and medication administration which is important for prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
194
8
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(235 citation statements)
references
References 33 publications
18
194
8
15
Order By: Relevance
“…Anaesthetic-related mortality in middle-income countries is 2-3 times higher than that in developed countries. 11,12,45,[47][48][49] Perioperative mortality trends may initially increase in middleincome countries with increasing access to surgical care, the increased provision of surgery for unwell patients undergoing complex procedures, and more reliable data. 9,11,12,19,29 A 2014 study from Brazil demonstrated this, as 24-hour perioperative mortality increased when compared against the incidence of mortality reported in previous studies.…”
Section: Incidence Of Morbiditymentioning
confidence: 99%
See 4 more Smart Citations
“…Anaesthetic-related mortality in middle-income countries is 2-3 times higher than that in developed countries. 11,12,45,[47][48][49] Perioperative mortality trends may initially increase in middleincome countries with increasing access to surgical care, the increased provision of surgery for unwell patients undergoing complex procedures, and more reliable data. 9,11,12,19,29 A 2014 study from Brazil demonstrated this, as 24-hour perioperative mortality increased when compared against the incidence of mortality reported in previous studies.…”
Section: Incidence Of Morbiditymentioning
confidence: 99%
“…9,11,12,19,29 A 2014 study from Brazil demonstrated this, as 24-hour perioperative mortality increased when compared against the incidence of mortality reported in previous studies. 11,47,50 Anaesthetic-related mortality increases by a factor of 50-100 in low-income countries, but may be 1 000-fold higher in certain poor countries. 11,18,19,21,[47][48][49][50][51][52][53][54][55] Bainbridge reported a similar trend in adult patients.…”
Section: Incidence Of Morbiditymentioning
confidence: 99%
See 3 more Smart Citations